Exploring the Role of DNase I as a Treatment for Alzheimer’s Disease. - Arredondo-Alcalá, María Ángeles; Vegas-Gómez, Laura; López Del Castillo, Inés; Garcia-Martín, Jesús; Moreno-González, Inés (My University, 2026)
Background: Most of the treatments for Alzheimer’s disease (AD) neither prevent its onset nor halt its progression, offering only temporary symptomatic relief. Therefore, identifying more effective therapeutic strategies and novel molecular targets remains crucial. Emerging evidence indicates that extracellular DNA (eDNA) —whether bacterial (derived from infections or the microbiota) or eukaryotic (released through neutrophil extracellular traps (NETs) or cell damage)— can promote β-amyloid aggregation and neuroinflammation, potentially contributing to AD pathogenesis. Recombinant human deoxyribonuclease I (rhDNase I), an enzyme that degrades DNA, may thus represent a promising therapeutic candidate for AD. Methods: To assess the therapeutic potential of rhDNase I in Alzheimer’s pathology, we administered weekly intraperitoneal injections of the enzyme to 5xFAD transgenic mice between 2 and 4 months of age. Following treatment, cognitive performance, amyloid burden, and neuroinflammation were assessed using behavioral tests and histological analyses to evaluate amyloid deposition and inflammation. Results: RhDNase I treatment markedly reduced both amyloid pathology and neuroinflammatory markers. However, no significant improvements were observed in cognitive performance of treated animals. Conclusions: The observed reduction in amyloid-related pathology following rhDNase I administration highlights extracellular DNA as a targetable factor to treat AD. Further studies are warranted to determine whether optimization of treatment timing, dosage, or combination with other therapeutic approaches could yield cognitive benefits.
Keywords: Alzheimer, Enfermedad de; Enzimas de restricción del ADN; Endonucleasa; Acido desoxirribonucleico extracromosómico; Alzheimer's disease; Neuroinflammation; Extracellular DNA; Recombinant human deoxyribonuclease I